Juridical Analyze of Citizen Mortality General Election 2024 in Surabaya - Ruslin Ruslin (Aloha International Journal of Multidisciplinary Advancement (AIJMU), 2023)
Elections are one form of demonization of the democratic system. Where the implementation of General Elections must be done carefully, and minimize some of the mistakes that exist. However, nowadays it has been found that there are dead citizens who are included in the voter list in Surabaya. The existence of these problems has certainly drawn criticism from the people at the Election Committee in Surabaya, considering that these problems can lead to fraud in the general election. If observed, basically the Surabaya Election Commission has carried out its duties properly and under existing laws and regulations. Where voter data collection carried out by the Surabaya Election Commission was carried out in several stages, including requesting population data from the Surabaya Civil Registry Office; Mapping and distribution of the Election Site conducted by the Election Committee; Updating and Verification conducted by Election Surveyor; Published to the public by sticking it in the place in the Sub District Office; and designated as the Permanent Voters List. So after observing in-depth three factors that cause these problems to emerge, including regulatory factors; family factors that died less orderly administration; and economic factors Keywords: citizens mortality, voter list